The leopard boy - Picouly, Daniel, 1948- (CARAF books., 2016)
"This prize-winning historical novel, set against the backdrop of the French Revolution, centers on the search by conflicting parties for a mottled-skinned boy rumored to be the son of Marie-Antoinette and a man of color. Of mixed-race parentage himself, Daniel Picouly offers a prescient re-creation of postcolonial France in light of its immigrant population"--